2008
DOI: 10.1002/er.1387
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new type of solar dryer: Its mathematical modelling and experimental evaluation

Abstract: SUMMARYA solar dryer fitted with a novel design of absorber having inbuilt thermal storage capabilities was designed, fabricated, simulated and also tested at Rajiv Gandhi College of Engineering Research & Technology, Chandrapur (MS) India. Thermic oil was used as a storage material. The main objective of the study was to reduce the drying period and enhance the quality of dried product mainly chillies and fenugreek leaves. The products were laid in a single layer. The dimensions of the dryer were arrived at u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Solid phase materials can be found, among others, in solar dryers with an oil tank [ 12 ], a battery made of concrete, as well as sand and rock bed [ 13 ]. The use of rocks as a material for filling a bed storage enables the construction of a simple drying installation that uses air as the working medium.…”
Section: Methodsmentioning
confidence: 99%
“…Solid phase materials can be found, among others, in solar dryers with an oil tank [ 12 ], a battery made of concrete, as well as sand and rock bed [ 13 ]. The use of rocks as a material for filling a bed storage enables the construction of a simple drying installation that uses air as the working medium.…”
Section: Methodsmentioning
confidence: 99%
“…In developing countries solar dryer of hot air type is the dominant method that is used for drying medicinal herbs. Recently, various of types of medicinal herbs have been dried using the solar dryers of hor air type such as: black ginger [9], lemon verbeva leaves [10], curcuma [11], mint [12], [13], rosella [14], [15], Valeriana jatamansi [16], red pepper [17], wild ginger [18], Centella asiatica [19], thymus and mint [20], jerky [21], Andrographis paniculata [22], green tea [23], fenugreek leaves [24], and onion slice [25].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Radajewski, Jolly, and Abawi (1987) proposed a computer model to reduce drying cost through optimisation of geometry and specific rate of air flow of solar assisted dryer system. In addition, dryer size optimisation studies of natural and forced convection solar dryer systems based on simulation models have been carried out to achieve minimum cost per unit moisture removal (Youcef-Ali and Desmons 2005;Potdukhe and Thombre 2008). Experimental investigations on open sun drying have also been carried out for determination of optimal surface area to volume ratio of breadfruit (Artocarpus altilis) for minimum drying time (George, McGruder, and Torgerson 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Singh, Singh, and Dhaliwal (2006) obtained efficiency in the range of 5-28% during three successive drying days of natural circulation multi-shelf perforated tray solar dryer for solar intensity of 150-800 W/m 2 and ambient air temperature of 20 • C. Forson, Nazha, and Rajakaruna (2007) tested the mixed-mode natural convection solar dryer for solar irradiance of 350 W/m 2 for different load and concluded that efficiency increased to 3.5-12.5% for load variation of 49-162 kg. Potdukhe and Thombre (2008) determined the efficiency in the range of 8-21% for indirect natural convection solar dryer with chillies under the ambient conditions of 25-40 • C and solar radiation 173-934 W/m 2 . Ben Slama and Combarnous (2011) studied the dependence of temperature and air velocity on drying kinetics of orange peels using solar dryer with slightly oblique baffles.…”
Section: Introductionmentioning
confidence: 99%